COLOUR NAMING DIVERSITY IN DESCRIPTIONS BY YOUNGER SCHOOL CHILDREN (Philological Studies, 2023)
In the phase of language acquisition process that starts when a child reaches the first year of age and lasts until the third year when a child has gained command over the basics of the mother tongue, nouns and verbs are the most important parts of speech that children use in the process of communication. Language acquisition will depend on a number of factors: a child's gender, the number of children in the family, a child's environment, the media they consume, the way older members of the family speak to the child, attending kindergarten, parents' education and the organic idiom that a child is exposed to. At that early age a child names everything that surrounds them thus gaining knowledge about the world around them. Colours are a part of a child's world and after naming things and people, the child starts acquiring the names of primary colours. In the same way, if a child is learning a foreign language, one of the first words to be learned are the names of the colours so the content of numerous cartoons intended for nursery school children is connected with colours. With time, a child expands their vocabulary acquiring new words, listening to stories and especially fairy tales that are rich with various adjectives and colour names in denotative and connotative meanings. It is interesting that children often use colours to describe people, exterior and interior space both in speaking and writing. Even though their knowledge about colours increases with age, in the active lexis there are very often only basic colours: blue, red, yellow, brown, black, white and green. Therefore, it is the goal of this research to examine how younger school children (7 to10-year- olds) use colours in their descriptions of people, exterior and interior space. The research was made in the form of an experiment taking place in the Croatian language (mother tongue) lesson during which the students had to activate the lexemes connected with colours using texts about colours and language play. After that, the students wrote compositions in which active use of colours in written expression was tested. The research confirmed the expectation that students use up to five basic colours in their speech and a small number of different adjectives which implies that younger school children's vocabulary size is getting smaller despite numerous spoken language impulses that children today receive.